Culture Negative Listeria monocytogenes Meningitis Resulting in Hydrocephalus and Severe Neurological Sequelae in a Previously Healthy Immunocompetent Man with Penicillin Allergy - Shahin Gaini; Gunn Hege Karlsen; Anirban Nandy; Heidi Madsen; Debes Hammershaimb Christiansen; Sanna á Borg (Case Reports in Neurological Medicine)
A previously healthy 74-year-old Caucasian man with penicillin allergy was admitted with evolving headache, confusion, fever, and neck stiffness. Treatment for bacterial meningitis with dexamethasone and monotherapy ceftriaxone was started. The cerebrospinal fluid showed negative microscopy for bacteria, no bacterial growth, and negative polymerase chain reaction for bacterial DNA. The patient developed hydrocephalus on a second CT scan of the brain on the 5th day of admission. An external ventricular catheter was inserted and Listeria monocytogenes grew in the cerebrospinal fluid from the catheter. The patient had severe neurological sequelae. This case report emphasises the importance of covering empirically for Listeria monocytogenes in all patients with penicillin allergy with suspected bacterial meningitis. The case also shows that it is possible to have significant infection and inflammation even with negative microscopy, negative cultures, and negative broad range polymerase chain reaction in cases of Listeria meningitis. Follow-up spinal taps can be necessary to detect the presence of Listeria monocytogenes.